The Effectiveness of Community Organizations (Ormas) in Maintaining Cultural Diversity in the Community of Gorontalo Village, Komodo District, West Manggarai Regency - Noor, Moch; Sugiantiningsih, Anak Agung Putu; Suyasa, I Made; Wirantini, Ni Ayu Kadek (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Wibowo & Harefa (2015), the form of implementation of everyone's right to gather, express opinions and associate is the formation of community organizations (Ormas). This was further realized with Law Number 16 of 2017 concerning amendments to Law Number 17 of 2013 concerning Community Organizations. Community Organizations, hereinafter referred to as Ormas, are associations created by the community and formed based on the same aspirations, goals and ideals based on voluntary aspects to participate in development as a form of support in achieving state goals based on Pancasila and the 1945 Constitution. Community Organizations have a function as intermediaries to provide aspirations and participation of the community in government, as a forum that provides protection to the community itself, functions to maintain customs and culture as well as religious values, preserve and maintain existing norms in society, both moral and ethical. , and culture that lives in society, and other functions stated in the applicable laws and regulations. The existence of mass organizations is expected to act as a mouthpiece for the people of the area who have united them. Culture is viewed in a completely aesthetic way. What Kleden explains, if it is related to the context of caci, mbata, sanda, danding, etc., seems to be challenged in the midst of today's cultural modernization. Therefore, such cultural heritage should be interpreted as a whole (totality) as a characteristic of Manggarai culture. In the context of caci, it is actually a strategic event in terms of promoting regional tourism. The dance of mutual whipping between adult men (caci) should have a legal basis in the form of regional regulations. This is the task of the regional parliament (DPRD) to make regional regulations. The method used in this research is a descriptive qualitative method which aims to describe the forms, uniqueness and variety of culture of the Manggarai people. The main instrument in this research is own research. The types of data used in this research are primary and secondary data, primary data is data obtained from interviews or observations. Meanwhile, secondary data is data obtained from the results of reviewing reference books or documentation. Community perception of the cultural diversity of Manggarai, especially Gorontalo Village, Komodo District, West Manggarai Regency, East Nusa Tenggara Province. The Gorontalo Village community is very enthusiastic about the cultural diversity of Manggarai by continuing to regenerate this cultural diversity in the younger generations so that cultural diversity continues to exist in the Manggarai community in general and in the Gorontalo Village community in particular.